(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Immobilization of radioactive waste is required to comply with nuclear regulations and waste acceptance criteria in a repository, which require the waste to be solid or immobilized in solid form within a durable and resistant matrix . Cement is the most frequently used material for the immobilization of liquid, low-level waste, since it has many advantages, such as the ease of preparation at room temperature and the low cost. In this paper, we describe the characteristics of cement-water mixtures, homogenized in a drum using a vibration table as the mixing device. Common Portland cement was used as the immobilization matrix. The homogeneity of the mixtures is evaluated using cement dye in appropriate amounts. Initially, the distribution of the mineral dye was made by visual inspection. The batches were carried out with three different ways of feeding the components. Different results were obtained depending on the feeding methods employed.